Application Of Differential Equations In Spherical Space - Mahbod, Mohammad; Mahbod, Mohammad Reza; Mahbod, Amir Mohammad (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Application of differential equations in spherical space has been approved in this paper. Regarding the importance of differential equations in mathematical mechanics , a reasonable relation is felt to be presented in order to design and optimize dynamic systems( dynamic mechanics) and all relevant subsets. This paper tries to establish the relation in question in the simplest possible state.